2014
DOI: 10.1002/ajmg.b.32272
|View full text |Cite
|
Sign up to set email alerts
|

Association and ancestry analysis of sequence variants in ADH and ALDH using alcohol‐related phenotypes in a Native American community sample

Abstract: Higher rates of alcohol use and other drug-dependence have been observed in some Native American populations relative to other ethnic groups in the U.S. Previous studies have shown that alcohol dehydrogenase (ADH) genes and aldehyde dehydrogenase (ALDH) genes may affect the risk of development of alcohol dependence, and that polymorphisms within these genes may differentially affect risk for the disorder depending on the ethnic group evaluated. We evaluated variations in the ADH and ALDH genes in a large study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…The analyses of changes in introns, e.g. studies conducted by Peng et al, which corroborated earlier results obtained by two study groups, indicate that changes within introns of the ADH7 gene frequently demonstrate a protective role against alcoholism [37].…”
Section: Archiwum Medycyny Sądowej I Kryminologii Archives Of Forensisupporting
confidence: 84%
See 1 more Smart Citation
“…The analyses of changes in introns, e.g. studies conducted by Peng et al, which corroborated earlier results obtained by two study groups, indicate that changes within introns of the ADH7 gene frequently demonstrate a protective role against alcoholism [37].…”
Section: Archiwum Medycyny Sądowej I Kryminologii Archives Of Forensisupporting
confidence: 84%
“…Analizy zmian w obrębie intronów, m.in. badania Penga i wsp., które potwierdziły wcześniejsze wyniki dwóch grup badawczych, wskazują, że zmiany w obrębie intronów genu ADH7 często wykazują rolę ochronną przeciwko alkoholizmowi [37].…”
Section: Discussionunclassified
“…The demographic information on the sample is provided in Table 1. A description of the sample has been reported previously (Ehlers et al 2004a(Ehlers et al ,2004bPeng et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…While SFFS cohort is primarily composed of European Americans, most AI participants have an admixed ancestral background (Norden-Krichmar et al, 2014, Peng et al, 2014). Additionally, both cohorts have family structures.…”
Section: Methodsmentioning
confidence: 99%
“…The present report is part of a larger study exploring risk factors for substance dependence in an American Indian community (Ehlers et al, 2004b, Gilder et al, 2004, Gilder et al, 2008) and a nationwide study on genetics of alcoholism and other substance dependence in a primarily European American population (Seaton et al, 2004, Vieten et al, 2004, Gizer et al, 2011b). We previously evaluated effects of variants in the ADH and ALDH genes on alcohol dependence phenotypes in a subset of the AI cohort, and found significant evidence for association with a severity level of alcohol drinking-related dependence symptoms phenotype across the ADH gene cluster (Peng et al, 2014). Our study also suggested that a higher degree of AI ancestry was associated with higher frequencies of potential risk variants.…”
Section: Introductionmentioning
confidence: 99%